Hybrid additive manufacture of 316L stainless steel with cold spray and selective laser melting: microstructure, mechanical properties and case study - Lupoi, Rocco; Yin, Shuo (ASM International, 2019)
A novel hybrid additive manufacturing process was proposed and utilized for the production of 316L stainless steel components in this work. It combines selective laser melting (SLM) and cold spraying (CS), allowing the fabrication of complex structures with SLM and the rapid manufacture of simple features with CS. The underlying principle of the hybrid additive manufacturing is to use CS to deposit a 316L stainless steel structure onto an SLM 316L stainless steel component, followed by heat treatment and finish machining. The microstructure and mechanical properties of the as-fabricated and heat-treated CS/SLM part, and the CS/SLM interfacial bonding features were studied. In the as-fabricated state, the CS part has a dendritic structure similar to the feedstock, while the SLM part is characterized by cellular subgrains confined in coarse grain structures. Due to recrystallisation after heat treatment, the definition of interparticle boundaries diminished, equiaxed coarse grains and twinning were formed, and the extremely fine cellular subgrains are removed from the SLM part. Due to the ‘fusion’ nature of the process, the SLM sample delivered improved mechanical properties when compared to the CS sample, even after heat treatment which significantly improves its mechanical properties. Heat treatment also improves the interfacial bond strength between the CS part and SLM part due to enhanced atomic diffusion. The case study demonstrates that the proposed hybrid additive manufacturing is a promising technique for the manufacture of free-standing components, modification of fabricated components and the repair of damaged components.
ITSC 2019 - Proceedings of the International Thermal Spray Conference
PUBLISHED
Yokohama (Japan)
Keywords: Selective laser melting (SLM); Cold spraying (CS); Hybrid additive manufacturing; Hybrid additive manufacturing process; 316L stainless steel components